Graphene-Modified 3D Copper Foam Current Collector for Dendrite-Free Lithium Deposition - Yu, Juan; Dang, Yangyang; Bai, Maohui; Peng, Jiaxin; Zheng, Dongdong; Zhao, Junkai; Li, Linbo; Fang, Zhao (Frontiers in Chemistry, 2019)
Lithium (Li) metal has been regarded as the ideal anode for the rechargeable Li-metal batteries such as Li-S and Li-air batteries. A series of problems caused by Li dendrites, such as low Coulombic efficiency (CE) and short circuit, have limited the application of Li-metal batteries. In this study, a graphene-modified three-dimensional (3D) Copper (Cu) current collector is addressed to enable dendrite-free Li deposition. After Cu foam is immersed into graphene oxide (GO) suspension, a spontaneous reduction of GO induced by Cu generates reduced graphene oxide on 3D Cu (rGO@Cu) substrate. The rGO@Cu foam not only provides large surface area to accommodate Li deposition for lowering the local effective current density, but also forms a rGO protective layer to effectively control the growth of Li dendrites. As current collector, the rGO@Cu foam shows superior properties than commercial Cu foam and planar Cu foil in terms of cycling stability and CE. The rGO@Cu foam delivers a CE as high as 98.5% for over 350 cycles at the current density of 1 mA cm−2. Furthermore, the full cell using LiFePO4 as cathode and Li metal as anode with rGO@Cu foam as current collector (LiFePO4/rGO@Cu-Li) is assembled to prove the admirable capacities and indicates commercialization of Li-metal batteries.